Compressive and tensile strength measurement of irreversible hydrocolloid impression material made of brown algae Padina sp - Nurlindah Hamrun; Rafikah Hasyim; Acing H. Mude; Muhammad Ikbal; Teiza Nabilah; Mutiaranisa Safitri; Fuad H. Akbar (DiscoverSys Inc., 2021)
Objective: This study aimed to explore the potential of brown algae (Padina sp) by measuring its compressive and tensile strength as a preparation step for making standardized dental impression materials from sodium alginate Padina sp.Methods: This study was a quasi-experimental study with one-shot case design. Brown algae were taken from the waters of Punaga and Puntondo, Takalar. Sodium alginate was extracted from algae then mixed with other compositions to form alginate impression material. Compressive and tensile were tested using the Point Load Test.Results: Compressive strength of impression material made of Padina sp was higher than that of standard impression material with pressure mean 0.011 Mpa and 0.009 Mpa. The mean tensile strength measurement was 0.003 Mpa.Conclusion: Mean compressive and tensile strength of impression material made of Padina sp were still relatively weak.